Factors Related to Nurses' Anxiety Regarding the Omicron Covid-19 Variant in Bangli Regency - I Made Agus Budi Wijaya (Babali Nursing Research)
Introduction : The COVID-19 pandemic, especially the Omicron Variant, has had a broad impact on human life, especially on the economic and health aspects, including for nurses who work at the forefront and are prone to experiencing anxiety. This study aimed to identify factors associated with nurses' anxiety toward the Omicron Variant of COVID-19. Methods: This study was conducted in the Bangli Regency of Bali, Indonesia. The sampling technique used was snowball sampling. The instrument was a questionnaire that was filled out by the respondents themselves through Google Forms. Univariate, bivariate (Chi-square test), and multivariate analyzes (multiple logistic regression) was performed for this research analysis. Result and Analysis: The results of this study found that 25.7% of respondents experienced anxiety toward the Omicron Variant of COVID-19. Perception and completeness of Personal Protective Equipment (PPE) were significantly associated with nurses' anxiety toward the Omicron Variant of COVID-19. Discuss and Conclution:  Nurses are very important to pay attention to two things such as the perception and completeness of PPE to prevent excessive anxiety for nurses who work on the front lines to serve general patients including COVID-19 patients.